Screening of biosurfactants from marine microorganisms - Al-Araji, Laith; Kadum, R. H. J (2011)
In this study, a total of 250 isolates was obtained from the seawaters of the coast of Kuantan, Pahang. Ten bacterial strains previously isolated were selected for the screening of biosurfactant producer(s) via three different characterization tests for biosurfactant; (i) surface tension measurements, (ii) emulsification activity, and (iii) cetyltrimethylammonium bromide assay (CTAB) test. One isolate coded SR171 to be the best candidate for biosurfactant production.